Teaching Methods for Reading Skill in Inclusive Class - Ajeng Sito Larasati; Muhammad Agung Nugroho (Universitas Cokroaminoto Palopo, 2021)
This study is aimed to investigate the teaching method used for reading skill in inclusive class. The type of study is categorized into a qualitative research designed in a case study. It is placed in an inclusive class at MAN 2 Klaten which consists of a mix among twenty eight normal learners and three special need learners on second semester in 2019/2020 academic year. The technique of collecting data is applied through observation, interview, and documentation. Then, the analyzing data is done by data reduction, data display, and verification based on the theory of Miles and Hubberman. The results shows that the teacher applies the traditional teaching methods namely Grammar Translation Method, Direct Method, and Cognitive Code Learning which reflect the humanistic way in teaching without exception among normal and special need learners in class. Those methods are very effective in developing the reading skill in inclusive class which focused to vocabulary mastery, active orally communication in a discussion, and grammar comprehension.